Molecular spin qubits based on lanthanide ions encapsulated in cubic polyoxopalladates: design criteria to enhance quantum coherence1. Issue 10 (29th October 2015) - Baldoví, José J.; Rosaleny, Lorena E.; Ramachandran, Vasanth; Christian, Jonathan; Dalal, Naresh S.; Clemente-Juan, Juan M.; Yang, Peng; Kortz, Ulrich; Gaita-Ariño, Alejandro; Coronado, Eugenio
<x xml:space="preserve">Abstract</x> Axial compression and a magnetic field can help to get coherent spin qubits.